KUALITAS AIR DAN KELIMPAHAN PLANKTON DI DANAU SENTANI, KABUPATEN JAYAPURA - Lismining P. Astuti; Andri Warsa; Hendra Satria (Universitas Gadjah Mada, 2009)
The Aims of this research were to know physical and chemical characteristic and plankton abundance of water in Lake Sentani. The research was done on September and November 2006 with stratified survey method. Samples were collected from four stations, namely Yope Bay, Butali Bay, Asei Besar and Kampung Harapan, at 0, 2, 4 and 8 m depth. Parameters were analyzed as temperature, transparency, dissolved oxygen, alkalinity, free CO2, N-NO2, N-NO3, P-PO4 and total organic matter. Water quality in Yope Bay, Butali Bay, Asei Besar and Kampung Harapan were show the same character. The averages of dissolved oxygen, total alkalinity, transparency were tend to high but free carbondioxide was low. The highest average of the phytoplankton abundance was found in Kampung Harapan about 104.423 ind/L and the highest average of zooplankton abundance was found in Asei Besar about 1.383 ind/L. Phytoplankton from Chlorophyceae dan zooplankton Copepoda were always found at every sampling stations.